Carbon ion radiotherapy: impact of tumor differentiation on local control in experimental prostate carcinomas - Glowa, Christin; Peschke, Peter; Brons, Stephan; Kiß, Oliver; Kopka, Klaus; Debus, Jürgen; Karger, Christian (Radiation oncology, 2017)
To summarize the research activities of the “clinical research group heavy ion therapy”, funded by the German Research Foundation (DFG, KFO 214), on the impact of intrinsic tumor characteristics (grading, hypoxia) on local tumor control after carbon (12C-) ion- and photon irradiations.